1 - Zaelani, Rizal; Patandung, Heri; Wiranta, Dadang (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
The aim of this study is to find out how the Current Ratio, Debt to Asset Ratio and Net Profit Margin partially and simultaneously influence the profit growth of manufacturing companies listed on the Indonesian Stock Exchange. (BEI). The study lasted five years, from 2017 to 2021. The research method used is quantitative. The sample was taken using the purposive sampling method. The data used is secondary data from the financial statements consisting of seven companies for the period 2017-2021. Double coefficient analysis, double linear regression, and statistical hypothesis testing are used partially and simultaneously. Research results show that the current ratio partially affects profit growth. Where the test results of the hypothesis show from the t count value 2,055 > t of the table 2,039 and a significant value of 0.048 < 0.05 so that H1 is accepted. Partially, the ratio of debt to asset does not affect Profit Growth. Where the result of the hypothetical test shows the thitung value 0.010 < t table 2.039 and the significant value is 0.992 > 0.05, so H2 is rejected. Net Profit Margin partially affects the growth of profits. Where the results of the hypothesis test show a t count value of 13,793 > ttable 2,039 and a significant value of 0,000 < 0,05 so H3 is accepted. Current Ratio, Debt to Asset Ratio and Net Profits Margin affect the growth in profits simultaneously. The test results of the hypothesis showed a significant value of 0,000 < 0.05 and F counting 71,034 greater than F table 2.90, so H4 was accepted.